Grotesque As Archetype of Poetic State In The Poetry of Frederik Rreshpa - Mandri , Hajri (International Journal of Scientific Research and Management (IJSRM), 2021)
Frederik Rreshpja, a famous Albanian poet, was born in Shkoder in 1940 and died in 2006. His   first literary work, the poetry collection, "Albanian Rhapsody" was published in 1967. He was imprisoned and served 17 years in prison during the communist regime.After he was released from prison, lived in Tirana and published the volumes "The time has come to die again" - 1994, "Selected lyrics" - 1996, a collection that was announced the best national book of the year, as well the volume of poetry "In solitude " was to be published in 2004.The focus of the article is on the features of the poetic style specifically on the grotesque as an author’s poetic preference that constitutes a special point of view of the author.The grotesque as an archetype of the poetic state in Rreshpa's poetry is conceived as a way of artistic reflection and as a style of writing. The key function of the metaphor-grotesque is the transfer, within the form of expression, from one context to another context with poetic undertones.Grotesque is a way of expression or way of presentation in which exaggerated sides are put together in powerful and unexpected contrast, or the most mixed, distorted and isolated forms of reality…